2010
DOI: 10.1016/j.jcf.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Serum tobramycin levels following delivery of tobramycin (Tobi®) via eFlow® advanced nebuliser in children with cystic fibrosis

Abstract: Serum tobramycin levels over 1mg/L can occur 1h post 300mg TOBI delivered by eFlow. Raised urinary NAG levels suggest that some children may have some associated early renal toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…No data exist for KIM‐1 and only few data are available in literature regarding NAG (reference) values in children with CF using TIS. One study measured NAG in urinary samples of 10 CF patients aged 2–16 years who received twice daily 300 mg TIS treatment with the eFlow nebulizer and 2 other studies reported NAG/creatinine ratios of, respectively, 4 and 14 patients in the age range of 3–22 years receiving 40–80 mg TIS twice daily with a jet nebulizer . Median NAG/creatinine ratios measured in our study were in the same order of magnitude as in the studies mentioned above.…”
Section: Discussionsupporting
confidence: 78%
“…No data exist for KIM‐1 and only few data are available in literature regarding NAG (reference) values in children with CF using TIS. One study measured NAG in urinary samples of 10 CF patients aged 2–16 years who received twice daily 300 mg TIS treatment with the eFlow nebulizer and 2 other studies reported NAG/creatinine ratios of, respectively, 4 and 14 patients in the age range of 3–22 years receiving 40–80 mg TIS twice daily with a jet nebulizer . Median NAG/creatinine ratios measured in our study were in the same order of magnitude as in the studies mentioned above.…”
Section: Discussionsupporting
confidence: 78%
“…Tobramycin- and aminoglycoside-induced ototoxicity reports range from nearly absent to approximately 35% of cystic fibrosis patients (Mulheran et al 2001, 2006; Piltcher et al 2003; Cheng et al 2009; Guy et al 2010; Martins et al 2010; Scheenstra et al 2010; Al-Malky et al 2011; Hennig et al 2014) with an increased risk of aminoglycoside-induced hearing loss with repeated and higher cumulative doses. The majority of adolescent and adult cystic fibrosis patients are colonized with Pseudomonas aeruginosa ( P. aeruginosa) (Cystic Fibrosis Foundation Registry 2011).…”
Section: Discussionmentioning
confidence: 99%
“…NAG is a proximal tubule lysosomal enzyme that has been extensively characterized as a sensitive, persistent, and robust urinary indicator of renal tubular injury . Urinary NAG levels have been used to evaluate the nephrotoxicity associated with different AG dosing regimens, and CF patients receiving inhaled AGs have been found to have increased urinary NAG levels . Although more limited, additional studies have shown increased urinary NAG levels in patients who were also receiving NSAID therapy …”
Section: Discussionmentioning
confidence: 99%